Teachers’ Pedagogical Transformation Towards 21st Century Learning in Enhancing Students’ Thinking Skills - Muhammad Izzat Mailis; Rosnidar Mansor (Pedagogia: Jurnal Ilmiah Pendidikan, 2025)
Learning in the 21st century has its own challenges and demands that teachers transform in their teaching. This study aims to examines how Malaysian teachers implement 21st Century Learning (21CL), focusing on teaching strategies, challenges, and the integration of Higher Order Thinking Skills (HOTs). Using a qualitative design, data were collected through interviews, classroom observations and lesson plan analysis involving purposively selected teachers. Findings show that teachers use various 21CL strategies such as collaborative, project-based and problem-based learning, digital tools and visual thinking techniques to promote HOTs and active student engagement. Implementation, however, is constrained by limited technological resources, unstable internet, insufficient teaching aids, low digital proficiency and environmental challenges such as large class sizes and limited time. Teachers with prior 21CL training applied the 4C elements which is Communication, Collaboration, Creativity, and Critical Thinking more consistently. The study highlights that effective 21CL practice requires teacher readiness supported by adequate infrastructure, ongoing professional development and strong school leadership. Implications for teaching, administration and policy are outlined, with recommendations for broader sampling, longitudinal studies and intervention research.